Perancangan Sistem Presensi Untuk Pegawai Dengan RFID Berbasis IoT Menggunakan NodeMCU ESP8266 - Kukuh Prasetiyo Aji; Ucuk Darusalam; Novi Dian Nathasia (Universitas Widyagama Malang, 2020)
At present there are still many government offices, especially the tourism and cultural offices of the Thousand Islands, which do not utilize technology for employee attendance, resulting in frequent manipulation of attendance data. Manual presence can cause the tourism office to have to manually record a large amount of attendance data, and make the process ineffective and inefficient. Therefore, this study aims to discuss the Employee Presence System Design with IoT (Internet of Things) Based RFID Using NodeMCU ESP8266. So this research can facilitate the Department of Tourism for the present system of attendance for employees to be more effective and efficient and does not take much time. This system is integrated with the website so that when the employee makes a presence, the data is automatically saved directly into the website database. Database processing on websites using MySQL with the PHP programming language. From several tests, many types of cards can be read by RFID Reader, because these